Arterial and Venous Pulmonary Vascular Morphology and Their Relationship to Findings in Cardiac Magnetic Resonance Imaging in Smokers. Issue 6 (November 2016) - Rahaghi, Farbod N.; Wells, J. Michael; Come, Carolyn E.; De La Bruere, Isaac A.; Bhatt, Surya P.; Ross, James C.; Vegas-Sánchez-Ferrero, Gonzalo; Diaz, Alejandro A.; Minhas, Jasleen; Dransfield, Mark T.; San José Estépar, Raúl; Washko, George R.
Abstract : Objective: Prior work has described the relationship between pulmonary vascular pruning on computed tomography (CT) scans and metrics of right-sided heart dysfunction in smokers. In this analysis, we sought to look at pruning on a lobar level, as well as examine the effect of the arterial and venous circulation on this association. Methods: Automated vessel segmentation applied to noncontrast CT scans from the COPDGene Study in 24 subjects with cardiac magnetic resonance imaging scans was used to create a blood volume distribution profile. These vessels were then manually tracked to their origin and characterized as artery or vein. Results: Assessment of pruning on a lobar level revealed associations between pruning and right ventricular function previously not observed on a global level. The right ventricular mass index, the right ventricular end-systolic volume index, and pulmonary arterial-to-aorta ratio were associated with both arterial and venous pruning, whereas right ventricular ejection fraction was associated with only arterial pruning. Conclusions: Lobar assessment and segmentation of the parenchymal vasculature into arterial and venous components provide additional information about the relationship between loss of vasculature on CT scans and right ventricular dysfunction.